2014
DOI: 10.3347/kjp.2014.52.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Helminthic Infections in Striped Field Mice,Apodemus agrarius, from Two Southern Regions of Korea

Abstract: The present study was performed to know the infection status of intestinal helminths in a most common species of field mice, Apodemus agrarius, from 2 southern regions of Korea. Total 133 and 103 mice were collected by the mouse trap in Hapcheon-gun, Gyeongsangnam-do and Gurye-gun, Jeollanam-do, respectively, from July 2005 to June 2006. The small intestine of each mouse was resected and longitudinally opened with a pair of scissors. The intestinal contents were washed with 0.85% saline until the supernatant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 13 publications
0
14
3
Order By: Relevance
“…In our study, the prevalence of N. brasiliensis ranged from 0% ( M. regulus ) to 70.9% ( A. agrarius ) (overall mean, 62.1%), depending on the species of rodent or soricomorph. This figure is quite different from previous studies performed in Korea [ 13 - 15 ]. Seo et al [ 13 ] and Yong et al [ 14 ] detected high prevalences of Nippostrongylus muris but not N. brasiliensis among rodents from northern and northern/western parts of Korea, respectively.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, the prevalence of N. brasiliensis ranged from 0% ( M. regulus ) to 70.9% ( A. agrarius ) (overall mean, 62.1%), depending on the species of rodent or soricomorph. This figure is quite different from previous studies performed in Korea [ 13 - 15 ]. Seo et al [ 13 ] and Yong et al [ 14 ] detected high prevalences of Nippostrongylus muris but not N. brasiliensis among rodents from northern and northern/western parts of Korea, respectively.…”
contrasting
confidence: 99%
“…Seo et al [ 13 ] and Yong et al [ 14 ] detected high prevalences of Nippostrongylus muris but not N. brasiliensis among rodents from northern and northern/western parts of Korea, respectively. On the other hand, Sohn et al [ 15 ] detected neither N. muris nor N. brasiliensis in A. agrarius mice from a southern area of Korea. The reason for this discrepancy remains to be investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is our understanding that the host list includes 11 animals belong to 6 families as follows: Canidae (Canis lupus and N. procyonoides), Felidae (F. catus), Ochotonidae (Ochotona dauurica), Muridae (A. agrarius, R. norvegicus, R. rattus, fortisM. pellceus, M. musculus), Mustelidae (M. itatsi), Procyonidae (P. lotor) and Suidae (S. scrofa) in Korea, China, Japan, Vietnam and the Russian Far East [12,[14][15][16][17][18][19][20][21][22][23][24][25]29]. However, only one species of mustelid, the Japanese weasel M. itatsi, has been reported as a host of I. hortensis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater snails of the family Lymnaeidae Rafinesque, 1815 are known to serve as first intermediate hosts [2][3][4], while freshwater fishes and frogs have been reported as second intermediate hosts [3,[5][6][7][8][9][10]. Addition-ally, a wide range of small mammals are known as respective definitive hosts, such as the rat (reported in Japan by Asada, 1926) [21], black-striped field mouse Apodemus agrarius (Pallas), Manchurian reed vole Microtus fortis pelliceus Thomas, domestic mouse Mus musculus L., brown rat Rattus norvegicus (Berkenhout), black rat R. rattus L., Daurian pika Ochotona dauurica (Pallas), domestc dog Canis lupus familiaris L., domestic cat Felis catus L., Japanese weasel Mustela itatsi Temminck (= Lutreola itatsi itatsi) and raccoon Procyon lotor L. [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Recently, Sohn et al reported two additional species, namely, the raccoon dog Nyctereutes procyonoides (Gray) and wild boar Sus scrofa L., to the list of known definitive hosts of I. hortensis [23].…”
Section: Introductionmentioning
confidence: 99%